Pengembangan Media Interaktif Berbasis Contextual Teaching and Learning pada Materi Bangun Datar Kelas IV Sekolah Dasar - Syafni Gustina Sari; Rahmayuni Jusar, Ira; Wahyuni, Sri (University of Muhammadiyah Malang, 2024)
This study aimed to develop interactive media based on Contextual Teaching and Learning (CTL) on the material two-dimensional figures for Grade V Elementary Schools. Technological developments require teachers to be more creative in developing learning media to suit the development of students who are